Characteristics of Thunderstorm Structure and Lightning Activity Causing Negative and Positive Sprites. Issue 15 (6th August 2018) - Yang, Jing; Liu, Ningyu; Sato, Mitsuteru; Lu, Gaopeng; Wang, Yu; Feng, Guili
Abstract: This paper reports observation of five sprites captured over a mesoscale convective system in a 15‐min window. One of them (11:49 hr sprite) was preceded by a negative cloud‐to‐ground with peak current of −40.9 kA that was detected both by the local lightning detection network (sprite time delay <70–90 ms) and the extremely low frequency (ELF) magnetic field data. Another sprite (11:46 hr sprite) was preceded by a negative stroke (sprite time delay <10 ms) with peak current of −106.6 kA but the ELF signal of the stroke could not be recognized. In addition, no positive strokes were recorded 1.5 min before the 11:46 hr sprite. The rest of the sprites were confirmed as positive both by the local lightning detection network and the ELF magnetic field data. The negative sprite occurred during strong convection, indicated by the increase of the area of the thundercloud with radar echo top of 8–11, 9–11, and 6–12 km. The strong convection and large wind shear in the thunderstorm middle and upper region provide favorable conditions to produce the parent cloud‐to‐ground lightning discharges of the negative sprites. Key Points: Detailed analysis of thunderstorm structure and lightning activity causing both negative and positive sprites has been made The roles of strong convection, wind shear, and stratiform region in producing sprite parent lightning have been confirmed Negative sprites can be produced by negative CG with moderate peak current